Association between glucocorticoid receptor beta and steroid resistance: A systematic review - Md. Mojahidur Hasan; Sehreen Tory (Immunity, Inflammation and Disease)
Abstract Background Glucocorticoids are the most commonly used anti‐inflammatory drugs for a variety of diseases, despite the fact that resistance to them is growing in a number of conditions. There is currently no biomarker that can be used to identify steroid resistance. According to a number of studies, an overexpression of the glucocorticoid receptor beta (GR‐β) isoform is associated with steroid‐resistant illness. Our goal is to find out whether or not steroid‐resistant disorders are associated with an increased level of GR‐β expression. Methods We conducted searches in the databases of Web of Science and PubMed until January 17, 2023. This systematic review was done according to the preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. The Joanna Briggs Institute Appraisal scale was used to assess the quality of the included studies. Results After the initial search, we identified 556 papers and finally included 20 studies. Twelve of these studies found an elevated level of GR‐β in the steroid resistant group. All five studies on asthma, two out of three on nasal polyps, both studies on ulcerative colitis found an up regulation of GR‐β in steroid resistant group as compared to steroid‐sensitive groups. GR‐β was also shown to be elevated in patients with allergic rhinitis, Crohn's disease and rheumatoid arthritis. In the majority of the investigations, higher levels of GR‐β were identified in peripheral blood mononuclear cells through the use of reverse transcription polymerase chain reaction. Conclusion GR‐β was associated with steroid‐resistant diseases. It was overexpressed in steroid‐resistant diseases and has the potential to be used as a biomarker for disorders involving steroid resistance.